Pengaruh Rekrutmen dan Penempatan Kerja terhadap Kinerja Pegawai pada Kantor Kecamatan Kemuning Palembang - Putri, Nur Liska Aliya (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effects of recruitment and job placement on employees' performance at Kemuning District Office in Palembang. Samples were selected using the saturated sample technique. Data of 45 respondents were collected through observation and questionnaires. This study implemented the multiple linear regression method to analyze data. The results of the investigation evidence that partially each recruitment and job placement has a significant effect on employees' performance. Likewise, simultaneously recruitment and job placement have a significant effect on employees' performance. This empirical evidence can provide benefits for the Kemuning District Office in Palembang. To improve employees' performance, the leader in this government institution should optimize recruitment and job placement factors.